Arabidopsis Responds to Alternaria alternata Volatiles by Triggering Plastid Phosphoglucose Isomerase-Independent Mechanisms . Issue 3 (23rd September 2016) - Sánchez-López, Ángela María; Bahaji, Abdellatif; De Diego, Nuria; Baslam, Marouane; Li, Jun; Muñoz, Francisco José; Almagro, Goizeder; García-Gómez, Pablo; Ameztoy, Kinia; Ricarte-Bermejo, Adriana; Novák, Ondřej; Humplík, Jan F.; et al.
Abstract : Cytokinin-mediated responses of Arabidopsis to volatile compounds emitted by pathogenic microorganisms involve the activation of plastidic phosphoglucose isomerase-independent mechanisms. Abstract: Volatile compounds (VC s) emitted by phylogenetically diverse microorganisms (including plant pathogens and microbes that do not normally interact mutualistically with plants) promote photosynthesis, growth, and the accumulation of high levels of starch in leaves through cytokinin (CK )-regulated processes. In Arabidopsis ( Arabidopsis thaliana ) plants not exposed to VC s, plastidic phosphoglucose isomerase (pPGI) acts as an important determinant of photosynthesis and growth, likely as a consequence of its involvement in the synthesis of plastidic CK s in roots. Moreover, this enzyme plays an important role in connecting the Calvin-Benson cycle with the starch biosynthetic pathway in leaves. To elucidate the mechanisms involved in the responses of plants to microbial VC s and to investigate the extent of pPGI involvement, we characterized pPGI-null pgi1-2 Arabidopsis plants cultured in the presence or absence of VC s emitted by Alternaria alternata . We found that volatile emissions from this fungal phytopathogen promote growth, photosynthesis, and the accumulation of plastidic CK s in pgi1-2 leaves. Notably, the mesophyll cells of pgi1-2 leaves accumulated exceptionally high levels of starch following VC exposure. Proteomic analyses revealed that VC s promote global changes in the expression of proteins involved in photosynthesis, starch metabolism, and growth that can account for the observed responses in pgi1-2 plants. The overall data show that Arabidopsis plants can respond to VC s emitted by phytopathogenic microorganisms by triggering pPGI-independent mechanisms.